Pengaruh Model TGfU Pada Pola Gerak Dominan Senam Terhadap Motivasi Belajar dan Waktu Aktif Belajar SMPN 1 Cimahi - Ilham Kholifah; Helmy Firmansyah; Tri Martini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to determine the effect of the Teaching Games for Understanding (TGfU) model on dominant movement patterns in gymnastics on students’ learning motivation and active learning time among seventh-grade students at SMP Negeri 1 Cimahi. The research method used is a quasi-experimental design with a pretest-posttest control group. The population of this study consisted of all seventh-grade students, and the sampling technique used was purposive sampling. The sample included 76 students, divided into two groups: 38 students in the experimental group and 38 students in the control group. Data on learning motivation were collected using a questionnaire that had been tested for validity and reliability (Cronbach’s Alpha = 0.943), while data on active learning time were obtained through the JWAB observation sheet. The results of the study indicate that the experimental group experienced an increase in the average learning motivation score from 151.79 to 172.08, with a significance value of 0.000 (p < 0.05). In addition, the active learning time in the experimental group reached 73.30%, which is higher than that of the control group at only 39%. In conclusion, the TGfU model is effective in improving students’ learning motivation and active learning time in gymnastics learning, as well as creating a more active, effective, and enjoyable learning environment. Keywords: Learning Motivation, PGD, Quasi-Experimental, TgfU, WAB